Acoustic immune reprogramming: a novel paradigm for spatiotemporally controlled immune regulation using ultrasound-responsive nanoplatforms - Chen, Tianyi; Chen, Junli; Chen, Mingkai; Song, Ruixiao; Wang, Mingsi; Yu, Xiaolong (Frontiers in Immunology, 2025)
The maintenance of immune homeostasis is a cornerstone of health, and mastering its regulation is now the focus of groundbreaking disease treatments. This review innovatively proposes and elucidates the “Acoustic Immune Reprogramming” framework: using ultrasound as a catalyst and nanoplatforms as carriers to enable hierarchical, spatiotemporally precise immune microenvironment interventions. It represents an advanced form of immunomodulation distinguished by its capacity for physical programming—the proactive and rational remodeling of cellular functions and tissue microecology with spatiotemporal precision and dose control unavailable to molecular agents alone. The review covers key technological advances in acoustic-mediated biological barrier penetration, local microenvironment programming, and precise delivery of drugs/genes/antibodies. It highlights functional remodeling of macrophages, neutrophils, dendritic cells (DCs), and the synergistic network effect. From a systems engineering perspective, acoustic nanoplatforms offer remote physical modulation, non-invasive activation, spatiotemporal control, and integrate bioinformatics, materials science, medical engineering, and AI. Three challenges are identified: (1) deciphering “black box” mechanisms via acoustic immune biology and single-cell multi-omics; (2) calibrating biological acoustic dosimetry for “physical input-to-immune effect” translation, plus personalized treatment prediction via cavitation standardization/digital twinning; (3) managing safety boundaries for “immune-programmable” nanomaterials and intelligent closed-loop systems. This review establishes the acoustic immune reprogramming framework, providing a theoretical basis for immune modulation/precision medicine and guiding interdisciplinary breakthroughs. Future advances may make acoustic “spatiotemporal immune sculpting” a cornerstone of intelligent medicine.